2021
DOI: 10.7554/elife.65774
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in transmissibility and shedding SARS-CoV-2 via droplets and aerosols

Abstract: Background: Which virological factors mediate overdispersion in the transmissibility of emerging viruses remains a longstanding question in infectious disease epidemiology.Methods: Here, we use systematic review to develop a comprehensive dataset of respiratory viral loads (rVLs) of SARS-CoV-2, SARS-CoV-1 and influenza A(H1N1)pdm09. We then comparatively meta-analyze the data and model individual infectiousness by shedding viable virus via respiratory droplets and aerosols.Results: The analyses indicate hetero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 136 publications
(249 reference statements)
6
99
0
2
Order By: Relevance
“…Symptomatic COVID-19 patients are more contagious regardless of the presence of close contacts [ 29 ], but asymptomatic patients run higher risks of spreading the virus to the general populace as they move around [ 30 ]. Asymptomatic infections are estimated to be 20% [ 31 ].…”
Section: Discussion: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…Symptomatic COVID-19 patients are more contagious regardless of the presence of close contacts [ 29 ], but asymptomatic patients run higher risks of spreading the virus to the general populace as they move around [ 30 ]. Asymptomatic infections are estimated to be 20% [ 31 ].…”
Section: Discussion: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…Aerosol transmission, direct contact transmission, and fomite transmission have been experimentally demonstrated in multiple animal models [ 49 , 338 343 ]. Furthermore, studies in non-human primates, and confirmed in humans, demonstrate that infected individuals exhale infectious aerosols, but this is highly variable across individuals and activities [ 344 , 345 ].…”
Section: Main Textmentioning
confidence: 99%
“…Highquality research is needed to better understand these aspects and attempt to estimate the relative contribution and importance of the transmission routes of SARS-CoV-2. However, this is challenging because of the complexities in transmission [49], including the fact that respiratory particles containing infectious SARS-CoV-2 are highly variable in different individuals and with different activities [344,345].…”
Section: Unknowns In Sars-cov-2 Transmissionmentioning
confidence: 99%
“…Occasionally multiple infections occur on a single flight [ 32 ]; but the majority of potential exposures on planes lead to no transmission [ 33 ]. These considerations point to COVID-19 transmission being highly heterogeneous, or “overdispersed”, a phenomenon with a building body of evidence [ 30 , 34 36 ].…”
Section: Introductionmentioning
confidence: 99%